Customers.com : how to create a profitable business strategy for the internet and beyond - Seybold, Patricia B. (Times Books New YorkUS, 1998)
Explains how to create a profitable electronic commerce strategy using a 5-step process that begins with making it easy for customers to do their business, and concludes with fostering customer loyalty. Details procedures for implementing 8 critical e-commerce initiatives and provides examples of successful cases. Includes initiatives such as: targeting the right customers; letting customers help themselves; delivering personalised service; and, fostering community.